RANCANG BANGUN ALAT PENGERING TIPE RAK SISTEM DOUBLE BLOWER - Rahbini Rahbini; Heryanto Heryanto; Basuki Rachmat; Erry Ika Rhofita (SENTIA 2016, 2016)
The drying process is done by most yam farmers in Indonesia by using conventional methods relying on sunlight. However, it does have many flaws that depends only on sunlight and weather changes so as to reduce the quality and interfere with the desired process. To improve the quality of the resulting yam flour is required drier. In this study focuses on design of yam drier rack type with double blower. The use of double blower on this instrument aims to establish a hot air flow patterns that can distribute the temperature evenly across the drying chamber, so that the drying process can take place quickly. Results of testing tools is done, the total energy requirement for drying chestnuts from the initial moisture content of 84% to 4.91% for 4 hours at 20118,823 kJ with total LPG consumption required for 0434 kg of LPG per hour and needs for 0109.